The Concept and Meaning of the Procedural Control of the Head of an Investigative Body in Criminal Proceedings - Smeshkova, Liliya; Moskovtseva, Kristina; Potapov, Vasily; Grinenko, Aleksandr; Ermakov, Sergey (Jurnal Cita Hukum, 2024)
In the article, the authors consider the most pressing issues relating to the conceptual framework of procedural control of the head of an investigative body and its importance in pre-trial criminal proceedings. The authors distinguish the correlation between the procedural control and departmental control exercised by the head of the investigative body. The authors substantiate that the science of criminal procedure needs theoretical consolidation of the correlation between procedural and departmental control, which is correlated as the general with the particular, where procedural control is understood as a special case of departmental control. In conclusion, based on the features highlighted by the authors, the author's wording of the concept of procedural control, which should be understood as based on the norms of criminal procedure law activity of the head of the investigative authority, carried out during the pre-trial proceedings in criminal cases, to implement the purpose of criminal proceedings, identifying, eliminating and preventing violations of criminal procedure and other legislation by the investigator, subject to the limits determined by procedural independence.